Strategi Adaptasi Pembudidaya Keramba Jaring Apung di Kolam Bekas Tambang di Desa Bangun Rejo Kecamatan Tenggarong Seberang - Kristoforus Lalong Setia Budi; Fitriyana Fitriyana; Gusti Haqiqiansyah (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
This study aims to determine the adaptation strategies carried out by kja farmers in ex-mining ponds, to see the social conditions of kja farmers and to find out the problems faced by kja farmers. The research location was chosen in the ex-mining pond of Bangun Rejo Village, Tenggarong Seberang District. The type of research data used in this study uses primary data and secondary data. The sampling technique used in this study was purposive sampling. The data analysis used is qualitative descriptive analysis. The results showed that there are several adaptation strategies carried out by kja farmers in ex-mining ponds so that the business continues to be sustainable, namely, selecting the right fish species, collaborating with related parties, managing water quality, making independent feed and expanding marketing networks. The social conditions of kja farmers can be seen from the aspects of education, livelihoods and cooperation between networks. Problems faced by kja farmers include difficulties in obtaining activity permits, lack of support from the government, rising feed prices and irregular payment of results.